Relationships of diet‐related blood parameters and blood lead levels with psychopathology and aggression in forensic psychiatric inpatients. (31st March 2015) - Zaalberg, Ap; Wielders, Jos; Bulten, Erik; van der Staak, Cees; Wouters, Anouk; Nijman, Henk
Abstract: Background: Earlier studies have suggested associations between diet‐related blood parameters and both aggression and psychopathological symptoms, but little is known about this in forensic psychiatric inpatients. Aim: This article aims to explore the levels of diet‐related blood parameters and their relationship to aggressive behaviour and/or psychopathology among Dutch forensic psychiatric inpatients. Methods: Minerals, vitamins, lead and fatty acid levels were measured in blood samples from 51 inpatients, well enough to consent and participate in the study, from a possible total of 99. Levels of aggression and psychopathology were assessed using questionnaires, observation instruments and clinical data. Associations between blood parameters and behavioural measures were calculated. Results: Low average levels of vitamin D3 and omega (ω)‐3 fatty acids were found, with nearly two‐thirds of the patients having below recommended levels of D3, while vitamin B6 levels were high. Magnesium, iron, zinc, copper and lead were overall within reference values, but copper/zinc ratios were high. Several significant associations between levels of fatty acid measures and both aggression and psychopathology were observed. Conclusion: In our sample of forensic psychiatric inpatients, fatty acids – but not mineral or vitamin levels – were associated with aggression and psychopathology. A potentially causal link between fatty acids and aggression could be tested in a randomised, placebo‐controlled trial of fish oil supplements. General health of such patients might be improved by better vitamin D status (increased sun exposure and/or supplement use) and better ω‐3 fatty acid status (oily fish or fish oil consumption), but discouraging unnecessary self‐prescription of B vitamins where necessary. Copyright © 2015 John Wiley & Sons, Ltd.